2019
DOI: 10.1039/c9ra07481c
|View full text |Cite
|
Sign up to set email alerts
|

Advancing fabrication and properties of three-dimensional graphene–alginate scaffolds for application in neural tissue engineering

Abstract: In this study, a bio-fabrication method has been developed for the preparation of 3D graphene–alginate composite scaffolds with great potential for neural tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 66 publications
2
21
1
Order By: Relevance
“…We have previously reported the mechanical, electrical and physical properties of engineered 3D composite scaffolds consisting of GO and sodium alginate (SA) (GOSA) [24]. Our study revealed that GOSA composite porous scaffolds combine the known advantages of alginate (including non-toxicity, biocompatibility, biodegradability) and graphene (including hydrophilicity, excellent mechanical strength, suitable biocompatibility, good electrical conductivity).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have previously reported the mechanical, electrical and physical properties of engineered 3D composite scaffolds consisting of GO and sodium alginate (SA) (GOSA) [24]. Our study revealed that GOSA composite porous scaffolds combine the known advantages of alginate (including non-toxicity, biocompatibility, biodegradability) and graphene (including hydrophilicity, excellent mechanical strength, suitable biocompatibility, good electrical conductivity).…”
Section: Introductionmentioning
confidence: 88%
“…The graphene-based composite scaffolds were fabricated by a technique involving solution mixing, freezedrying, crosslinking, and bio-reduction as described previously [24]. Briefly, 2 wt.…”
Section: Gosa/rgosa Scaffold Fabrication and Preparationmentioning
confidence: 99%
“…Particularly, alginate-based hydrogels do not permit good control over their internal architecture, they lack cell receptors adhesion sites and suffer from low protein adsorption capability [ 104 ]. As independently highlighted by Losic et al and Chen et al [ 105 , 106 ], the introduction of GO and RGO in an alginate matrix allows to modify and control the porosity of the gel (ca. 99%±0.3%), making the pores size uniform from surface to its inner core and fostering cellular activity.…”
Section: Graphene-based Scaffoldsmentioning
confidence: 99%
“…Poor dispersion of GBMs within the polymer matrix causes aggregation [ 105 ], which may be detrimental for scaffold properties. To achieve homogeneous and stable dispersions of GBMs, covalent and/or non-covalent functionalization may be required.…”
Section: Graphene-based Scaffoldsmentioning
confidence: 99%
“…In addition, the quality of tissue regeneration strongly depends upon the mechanical properties of the scaffold 3 . Scaffolds should be strong enough to support tissue regeneration and satisfactorily maintain their integrity during cell growth but not so rigid as to cause adverse tissue response 5,6 . The mechanical properties of the scaffolds should also mimic the mechanical strength of the native tissue 5 …”
Section: Introductionmentioning
confidence: 99%